Educator Ethics: Abdul Fattah Abu Ghuddah's Perspective In The Book of Ar-Rosuul Al-Mu'allim Wa Asaalibuhu Fi At-Ta'liim - Lingga, Salman Al-Farisi; Ritonga, Sakti; Ritonga, Asnil Aidah (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2025)
This study examines the ethics of educators according to Sheikh Abdul Fattah Abu Ghuddah in the book "Al-Mu'allim Wa Asalibuhu fi At-Ta'lim" and its relevance to the code of ethics for teachers in Indonesia. The main objective is to explore the suitability of the ethics discussed by Abu Ghuddah with the code of ethics for teachers in Indonesia, as well as the adaptation and integration of the religious values taught to enrich the code of ethics. This research is a concept analysis using primary data from the book "Ar-Rasul Al-Mu'allim Wa Asalibuhu fi At-Ta'lim" by Abu Ghuddah and its translation by Abu Husamuddin, as well as secondary data from various relevant literatures. Data collection went through four stages: preparation, bibliography preparation, time management, and research recording, with literature techniques that included understanding the topic, searching for supporting information, organizing reading materials, and recording in-depth research. Data analysis was conducted using the content analysis method. The results show that the Indonesian teachers' code of ethics emphasizes compassion, integrity, professionalism, and justice and is highly relevant to Abu Ghuddah's principles. Although Abu Ghuddah's approach is more religious, the values can be adapted and integrated into the more secular Indonesian teachers' code of ethics. This research enriches the code of ethics for educators in Indonesia by combining values. The adaptation of these values in the multicultural and pluralistic context of Indonesia can create a more meaningful, inclusive learning environment that is in line with the principles of inclusive education, producing a generation that is intellectually intelligent and has strong morals and ethics.